A Spectrum of Inclusion: Climate and Environmental Justice Teaching in a Technical Context - Christopher Rabe; Madeline Schlegel; Julia Reich; Ashanti Mclean; Olivia Girand; Claire Webster; Sabrina Araujo-Elorza (Journal of Environmental Studies and Sciences, 2026)
Although a substantial body of research has examined how sustainability is integrated into higher education curricula, relatively few studies have explored how instructors incorporate climate and environmental justice (CEJ) content and pedagogies across disciplines. Emerging scholarship has begun to address how interdisciplinary environmental and sustainability (IES) programs and institutional sustainability requirements include environmental justice (EJ) course content. Yet when CEJ knowledge is not broadly embedded across disciplines by IES faculty or institutional leaders, the resulting curricular gaps often exclude the content, practices, and lived experiences of those most affected by global environmental and climate challenges. This exclusion, especially common in STEM-focused areas, can have significant consequences for underrepresented students. This study investigates these dynamics within a STEM institutional context, examining how faculty and instructors incorporated CEJ content and pedagogy across 11 courses at a four-year, private, technical institution. Using a case-study approach and multiple data sources, the study identifies four clusters within a spectrum of CEJ inclusion, each characterized by distinct experiential pedagogies such as community engagement, transdisciplinary methods, and the use of diverse epistemologies. The findings also reveal that CEJ content was most often integrated into STEM courses through collaboration with the social sciences and humanities. Based on these results, the authors offer recommendations for instructors and campus leaders, including improving CEJ visibility in course catalogs, strengthening CEJ integration within STEM and computer science, expanding initiatives and training focused on community engagement, and formally recognizing the contributions of community partners through instructional titles.

Environmental justice teaching in an undergraduate context: examining the intersection of community-engaged, inclusive, and anti-racist pedagogy - Christopher Rabe (Journal of Environmental Studies and Sciences, 2024)
Since the early 1980s, the environmental justice (EJ) movement was critical in drawing much needed attention on how Black, Indigenous, People of Color (BIPOC), and low-income groups have experienced a disproportionate burden of environmental harms. This movement eventually formed the field of environmental justice, a multidisciplinary area of study that attempts to identify environmental injustices and provide theory and practice for their resolution. Despite the expansion of the EJ field and recent public attention, research shows that both EJ content knowledge and BIPOC students are isolated and excluded from Interdisciplinary, Environmental, and Sustainability (IES) programs within higher education. In addition, these studies have shown a relationship between EJ content and community-engaged practices with the inclusion of BIPOC students. This study sought to examine how and why EJ teaching and community-engaged pedagogies may be associated with inclusive or anti-racist practices by examining four faculty members teaching undergraduate EJ courses at four institutions. Using a multi-case study design, primary findings showed that faculty members held activist course objectives, which led to distinct community-engaged practices, such as the invitation of diverse guest educators, inclusion of readings from diverse authors, field experiences with EJ communities, and the integration of alternative ways of knowing that resist Eurocentric biases. The discussion and implications explore how these practices intersect with inclusive and anti-racist pedagogies, and provide recommendations for their implementation within the context of Environmental Studies and Sciences (ESS) in higher education.

Ecological carrying capacity in mariculture: Consideration and application in geographic strategies and policy - Jeffrey Fisher; Dror Angel; Myriam Callier; Daniel Cheney; Ramon Filgueira; Bobbi Hudson; Christopher W. McKindsey; Lisa Milke; Heather Moore; Francis O’Beirn; Jack O’Carroll; Berit Rabe; et al. (Marine Policy, 2023)

Aerosol emissions of a ship diesel engine operated with diesel fuel or heavy fuel oil - Thorsten Streibel; Jürgen Schnelle-Kreis; Hendryk Czech; Horst Harndorf; Gert Jakobi; Jorma Jokiniemi; Erwin Karg; Jutta Lintelmann; Georg Matuschek; Bernhard Michalke; Laarnie Müller; Jürgen Orasche; et al. (Environmental Science and Pollution Research, 2017)